2003
DOI: 10.1161/01.cir.0000097114.11038.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posture on Blood and Intraocular Pressures in Multiple System Atrophy, Pure Autonomic Failure, and Baroreflex Failure

Abstract: Background-Intraocular pressure (IOP) may be partially under systemic vascular control. This study examined whether a correlation exists between blood and intraocular pressures in patients with autonomic dysfunction. Methods and Results-Eleven patients with 3 types of confirmed autonomic dysfunction (multiple system atrophy, pure autonomic failure, and baroreflex failure) were compared with age-and gender-matched controls and had IOP, systolic blood pressure, diastolic blood pressure, heart rates, and calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…The third limitation is that we did not assess blood pressure, and some authors have pointed out its relevance to the posture-induced IOP change. 7,29,30 In summary, there was no significant difference in postureinduced IOP changes among mostly medically treated eyes with OAG, PAC, and normal control eyes. The posture-induced IOP change also varied individually, which may explain why significant changes were not found.…”
Section: Discussionmentioning
confidence: 83%
“…The third limitation is that we did not assess blood pressure, and some authors have pointed out its relevance to the posture-induced IOP change. 7,29,30 In summary, there was no significant difference in postureinduced IOP changes among mostly medically treated eyes with OAG, PAC, and normal control eyes. The posture-induced IOP change also varied individually, which may explain why significant changes were not found.…”
Section: Discussionmentioning
confidence: 83%
“…Although the exact interplay between blood pressure and IOP is still unclear, the altered response in blood pressure due to the baroreflex may influence or accompany changes in aqueous humor dynamics and IOP. Singleton et al, 21 have reported that in patients who had orthostatic hypotension with autonomic imbalance, postural change produced significant IOP changes by sudden fluctuation of blood pressure. Aging is known to be associated with a decreased sensitivity of the parasympathetic but not the sympathetic arm of the baroreflex.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in height is thought to affect the episcleral venous pressure. [6][7][8][9] The increase of resistance in the aqueous out-flow is probably the cause for the IOP increase in the SUP. 10 The IOP measurement in the SUP is important in several situations, such as the establishment of a real circadian curve.…”
mentioning
confidence: 99%